Pemanfaatan Augmented Reality Untuk Media Pembelajaran Alat Transportasi Bagi Anak Tunagrahita Sedang - Dimas Dwi Kurniawan; Donny Avianto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
A comparison between conventional teaching methods and modern technology reveals a significant difference in the effectiveness and efficiency of educating moderately mentally handicapped children or D3 C class. The available learning materials lack innovation. Monotonous material design that doesn't support interactivity can reduce the interest and engagement of mentally handicapped children. Therefore, the development of more engaging materials that meet their needs is required. D3 C class students with intellectual disabilities require special attention in the use of educational media, considering the current learning materials tend to be monotonous and lacking innovation. Therefore, Augmented Reality (AR)-based learning media can be a promising solution to enhance the quality of learning about various modes of transportation. Interactive AR-based applications enable the introduction of various modes of transportation in a more engaging and interactive way, involving visual and auditory aspects in learning. In application testing, it was proven that the speed of displaying 3D objects was very fast, taking only 2.3 seconds. This contributes to smooth and effective learning for D3 C class mentally handicapped children. Surveys conducted with teachers who have used this AR application indicate a tendency towards positive responses, with the majority of teachers responding